2016
DOI: 10.1890/15-0635.1
|View full text |Cite
|
Sign up to set email alerts
|

Plant and root endophyte assembly history: interactive effects on native and exotic plants

Abstract: Abstract.Differences in the arrival timing of plants and soil biota may result in different plant communities through priority effects, potentially affecting the success of native vs. exotic plants, but experimental evidence is largely lacking. We conducted a greenhouse experiment to investigate whether the assembly history of plants and fungal root endophytes could interact to influence plant emergence and biomass. We introduced a grass species and eight fungal species from one of three land-use types (undist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…In a greenhouse experiment, Sikes et al. () introduced grasses and fungal species before others and found that small differences in early arrival history during the first 2 weeks of assembly were sufficient to affect plant performance for 6 months. Moore and Franklin () found in a controlled experiment that root biomass of established species was reduced after water stress, but this outcome was dependent of priority effects and species identity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a greenhouse experiment, Sikes et al. () introduced grasses and fungal species before others and found that small differences in early arrival history during the first 2 weeks of assembly were sufficient to affect plant performance for 6 months. Moore and Franklin () found in a controlled experiment that root biomass of established species was reduced after water stress, but this outcome was dependent of priority effects and species identity.…”
Section: Discussionmentioning
confidence: 99%
“…Sikes et al. () also found that small differences in early arrival history, during the first 2 weeks of assembly, were sufficient to affect plant above and below‐ground performance for 6 months. Studying the effects of order of arrival among native species, Moore and Franklin () found in controlled experiments that the root biomass of later species were reduced after flooding and drought compared to species that arrived first, while Körner et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…So far experiments manipulating plant species order of arrival have mainly used controlled experimental set-ups using pots or mesocosms (Ejrnæs et al, 2006; Chase, 2010; Moore and Franklin, 2011; Stevens and Fehmi, 2011; Dickson et al, 2012; Byun et al, 2013; Kardol et al, 2013; Mason et al, 2013; Ulrich and Perkins, 2014; Burkle and Belote, 2015; Wilsey et al, 2015; Sikes et al, 2016). Focusing on order of arrival of different PFGs, Körner et al (2008) set up an experiment with nine grassland species from three different groups (non-leguminous forbs, legumes, and grasses), sowing one group before the other two.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the present theory, small differences during the early stage of plant–endophyte community assembly were sufficient to affect the plant condition for a long time (Sikes et al . ). Thus, in this work, the endophyte‐induced effects on straw decomposition were likely to accumulate throughout all the stages.…”
Section: Discussionmentioning
confidence: 97%